Ecological characterization of tree species for guiding forest management decision in seasonally dry forests in Lomerío, Bolivia - Pinard, M.A.; Putz, F.E.; Rumíz, D.; Guzmán, R.; Jardim, A. (1999)
When the goal of natural forest management is to maintain the biodiversity and ecological integrity of the forest while harvesting timber, the silvicultural systems employed must promote timber production and reduce negative impacts on whole timber resources. To foster development of such a system in a seasonally dry tropical forest in Lomerío, Bolivia, we classfied tree species according to their relative timber value, importance as food for vertebrate frugivores and vulnerability to population declines when subjected to logging. We used this classification to identify a management system appropriate for the commercial species and to evaluate the compatibility of the system with the regeneration requirements of tree species that produce important food for mammalian wildlife. About half of the tree species in the site are commercially valuable for their timber and a similar proportion are considered of value as food for wildlife. A tree species rating for vulnerability to disturbance appeared to be independent of both timber and wildlife values. A silvicultural system that includes even-aged groups of trees within an uneven-aged matrix appears more suitable to the multiple goals of management in this forest than either an even-aged or uneven-aged (single tree selection) management system.